ANALYSIS OF COCONUT FIBER REINFORCED COMPOSITES WITH HOT PRESS TECHNIQUES - Darmanto, Seno; Nugroho, Alvin Dio; Fathurrohman , Nur Kholis; Saputra , Imam; Kusni, Muhammad; Muflikhun, Muhammad Akhsin (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2024)
Natural fibre waste is a material with high material resistance, including fibres derived from coconut fruit. Coconut fruit waste is frequently underutilised and can contribute to environmental pollution if not handled correctly. This study's objective is to convert waste from coconuts into fibres, incorporate them into composite mixtures, and produce robust materials. Using coconut fibre presents a significant advantage in that it is easily biodegradable, reducing environmental pollution. The aim of this research is to produce a composite board material using HDPE plastic and coconut fibre, which is resistant to corrosion, through the hot felting method. This method of producing composite materials results in minimal voids and high material density, effectively reducing the chances of material failure. The composite specimens were subjected to testing following the ASTM D 638-01 standard. Technical abbreviations used throughout the text will be explained upon first use. The study achieved an excellent average tensile strength, strain, and elastic modulus of 22.45 MPa, 7.15%, and 5.13 MPa, respectively. The manufacture of composite materials using coconut coir fibre combined with HDPE plastic through the hot felting method resulted in high material strength, corrosion resistance, and reprocessability.